Penerapan Algoritma K-Means Untuk Menentukan Jumlah Produksi Kayu Bulat Berdasarkan Jenis Kayu Di Provinsi Jawa Barat - Sadewo Ahmad, Habib (Jurnal Teknik Indonesia, 2023)
Introduction: According to data from the Central Bureau of Statistics (BPS), log production fluctuated every quarter of 2020. Log production experienced a decline in the second quarter from a total production of 14.58 million m3 in the first quarter to 13.87 million m3. Purpose: to apply the K-Means data mining technique which is classified as a potential log production based on wood species with high and low criteria. Method: The type of research to be used is quantitative research. Discussion result: based on data on production and types of logs from 2016 to 2020, the West Java Forestry Service, log production in each district/city area in West Java is not evenly distributed for products and types of logs processed, therefore with the application of the K-Means algorithm is expected to help the production potential and types of logs in the West Java region. Therefore, the West Java Forestry Service determines the grouping of logs based on wood species into 2 clusters, namely high and low. Conclusion: The data is calculated based on 2 clusters, namely clusters with low potential (C1) and clusters with high potential (C2). The Forest Management Unit (KPH) area with the highest log production potential (C2) is the North Bandung KPH.